2019
DOI: 10.1038/s41598-018-36689-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of childhood maltreatment on epigenetic regulation of stress-response associated genes: an intergenerational approach

Abstract: While biological alterations associated with childhood maltreatment (CM) have been found in affected individuals, it remains unknown to what degree these alterations are biologically transmitted to the next generation. We investigated intergenerational effects of maternal CM on DNA methylation and gene expression in N = 113 mother-infant dyads shortly after parturition, additionally accounting for the role of the FKBP5 rs1360780 genotype. Using mass array spectrometry, we assessed the DNA methylation of select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 61 publications
1
43
2
Order By: Relevance
“…The deleterious consequences of prenatal maternal stress not only affect the first generation of newborns, but also may be transmitted across subsequent generations (24,25). In fact, recent animal studies have shown that gestational stress across generations has downstream effects on the endocrine and metabolic pathways (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…The deleterious consequences of prenatal maternal stress not only affect the first generation of newborns, but also may be transmitted across subsequent generations (24,25). In fact, recent animal studies have shown that gestational stress across generations has downstream effects on the endocrine and metabolic pathways (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…TEs can also influence genetic expression through epigenetic mechanisms. Furthermore, exposure to other previous adverse experiences increases the risk of PTSD development [ 13 ], through epigenetic mechanisms [ 8 ]. SNPs can also interact with environmental exposure and epigenetic modifications to increase the risk of PTSD development [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dysregulation of this response can lead to many health problems [9]. Furthermore, adverse childhood experiences (ACEs)-which dysregulate the hypothalamic-pituitary-adrenal axis [10]-are prevalent among primary care patients with chronic conditions and have been found to be positively correlated with the number of clinic visits and time to screen, which means that trauma-informed healthcare has become mandatory [11][12][13]. In this perspective paper, the authors aim to review the most relevant studies which support the hypothesis that trauma-informed healthcare is essential for GPs' clinical practice.…”
Section: Introductionmentioning
confidence: 99%